Project-based Authentic Assessment Needs Analysis for Teachers in Primary Schools - Yuyun Dwi Haryanti; Sapriya Sapriya; Anggy Giri Prawiyogi; Ahmad Rifqy Ash-Shiddiqy; Raden Sudarwo (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractLearning and assessment are an inseparable whole. Assessment, if designed appropriately, thoroughly and used appropriately in assessment procedures, can contribute to effective learning and have an impact on the competence of quality students. This study aims to analyze the need for project-based authentic assessment of teachers in elementary schools. This research includes descriptive qualitative research on elementary school teachers in Banjarnegara Regency, Central Java. Data was collected through literature studies of reputable international articles indexed by Scopus and field studies through questionnaires distributed to 103 elementary school teachers, interviews, and documentation studies of 10 elementary school teachers. Data analysis using the Miles and Huberman model includes: data collection, data reduction, data presentation, and conclusions. The results of the study showed that the majority of teachers' assessments focused on the knowledge aspect using a multiple-choice test, the attitude aspect using observation, and the skill aspect using project assessment. Due to a lack of references, teachers struggle to develop assessment instruments and thus lack a clear rubric. The conclusion of this study is that teachers have difficulty implementing project-based authentic assessments so they need a practical authentic assessment companion book.Keywords: authentic assessments, project-based, primary school teacher.AbstrakPembelajaran dan penilaian menjadi satu kesatuan yang tidak dapat dipisahkan. Penilaian bila dirancang dengan tepat, menyeluruh dan digunakan secara tepat dalam prosedur penilaian dapat berkontribusi pada pembelajaran yang efektif serta berdampak pada kompetensi peserta didik yang berkualitas. Penelitian ini bertujuan untuk menganalisis kebutuhan penilaian autentik berbasis proyek terhadap guru di sekolah dasar. Penelitian ini termasuk penelitian kualitatif deskriptif terhadap guru Sekolah Dasar di Kabupaten Banjarnegara, Jawa Tengah. Data dikumpulkan melalui studi literatur artikel internasional bereputasi terindeks scopus dan studi lapangan melalui kuesioner yang dibagikan terhadap 103 guru SD, wawancara, dan studi dokumentasi terhadap 10 guru SD. Analisis data menggunakan model Miles dan Huberman meliputi: pengumpulan data, reduksi data, penyajian data, dan kesimpulan. Hasil penelitian menunjukkan bahwa bentuk penilaian mayoritas guru pada aspek pengetahuan menggunakan tes pilihan ganda, aspek sikap dengan menggunakan observasi, dan aspek keterampilan diukur dengan penilaian proyek. Guru kesulitan dalam mengembangan instrumen penilaian sehingga tidak memiliki rubrik yang jelas diakibatkan kurangnya referensi. Simpulan penelitian ini bahwa guru kesulitan menerapkan penilaian autentik berbasis proyek sehingga membutuhkan buku pendamping penilaian autentik yang praktis.Kata kunci: penilaian autentik, berbasis proyek, guru sekolah dasar.